Analisa Faktor OEE pada Departemen Repacking di PT. X - David David; Felecia Felecia (Jurnal Titra, 2022)
PT.X is one of the largest agri-food companies in Indonesia. In its development, PT. X carries out animal feed production, maintenance, and poultry processing activities. PT. X has several departments, one of them is repacking department. Repacking department is a department in charge of packaging the animal feed products. However, there are some problems for data input process in repacking department. The data processing is still not integrated, structured, and also causing some waste. The waste that occurs include waste of time, cost, and energy. Seeing this problem, it is necessary to make an integrated and structured data summary so it can be used to analyzing the problems.In its stage, the process of compilling the data will be assisted by the Overall Equipment Effectiveness (OEE) method. The analysis process will be carried out with three main factors, namely availability factors, performance efficiency, and rate of quality product. Each factor value calculation in the data overview will be displayed in the form of data visualization to help users for drawing conclusions. The result of the data overview can help the companies to understand the condition in the field and also help users to follow-up on problems that occurs in repacking department.